Réponses

2012-11-19T20:41:13+01:00

5x-4 = x+4

5x-x = 4+4

4x= 8 donc x = 8/4 = 2

 

(7x+3)(x+1) = 0

soit (7x +3)=0 donx 7x = -3 donc x = -3/7

soit x+1 = 0 donc x = -1

 

(2x+4)(x-1) = 0 même chose ton produit est nul si l'un des 2 membres est nul donc soit

(2x+4) = 0 donc 2x = -4 donc x = -2

soit (x-1) = 0 donc x = 1

2012-11-19T22:42:43+01:00

5x-4=x+4

5x-x=4+4

4x=8

x=2

 

(7x-3)(x+1)=0

7x-3=0 et x+1=0

7x=3   et x=-1

x=3/7 

 

(2x+4)(x-1)=0

2x+4=0 et x-1=0

2x=-4    et x=1

x=-2